STEREOTIPE GENDER DALAM GAMBAR ILUSTRASI BUKU TEKS SEKOLAH DASAR - Kasiyan Kasiyan (LPPM UNY, 2001)
Abstract This research aims to reveal and to refine attendance meaning of the gender stereotype in the illustrative pictures of Elementary School textbook, based on curriculum 1994, with male object, female object, and male-female objects. From the existing tendency description, the social relation quality of the equal or unequal can be analyzed. This research uses a quantitative-descriptive perspective approach, particularly with a content analysis method. The research objects are all illustrative picture of all elementary school textbooks, based on curriculum 1994, published by Education and Culture department. They involve six textbook groups, id est. 1) Civic Education 2) Natural Science 3) Social Science 4) Body and Health Education, 5) Indonesian and 6) Mathematics. Those pictures, then, are classified sequentially, into some kinds, id est. Textbooks, picture categorization, and seven areas of development analysis (Women Affair Minister Office, 1995). The instrument used in collecting data is documentation-based guideline, which is developed by coding system. The data analysis is the description of frequency distribution and percentage models. From the research results, the research concludes that the illustrative picture with male objects tend to have male gender stereotype meaning, with female objects tend to have female gender stereotype, and with male-female objects reflects a gender equality. The implication of the research results and conclusion recommends that, in the future, there will be an improvement of the elementary school illustrative textbooks quality, with larger gender equality perspective, in order to make students understand the right concept of gender as early as possible. Moreover it needs a more extended research in the form of developing an illustrative picture design guideline that reflects gender equality. Keywords: gender stereotype, illustrative picture, and textbook